High HER2 protein levels correlate with increased survival in breast cancer patients treated with anti‐HER2 therapy. Issue 1 (15th September 2015) - Nuciforo, Paolo; Thyparambil, Sheeno; Aura, Claudia; Garrido-Castro, Ana; Vilaro, Marta; Peg, Vicente; Jimenez, José; Vicario, Rocio; Cecchi, Fabiola; Hoos, William; Burrows, Jon; Hembrough, Todd; et al.
Abstract : Introduction: Current methods to determine HER2 (human epidermal growth factor receptor 2) status are affected by reproducibility issues and do not reliably predict benefit from anti‐HER2 therapy. Quantitative measurement of HER2 may more accurately identify breast cancer (BC) patients who will respond to anti‐HER2 treatments. Methods: Using selected reaction monitoring mass spectrometry (SRM‐MS), we quantified HER2 protein levels in formalin‐fixed, paraffin‐embedded (FFPE) tissue samples that had been classified as HER2 0, 1+, 2+ or 3+ by immunohistochemistry (IHC). Receiver operator curve (ROC) analysis was conducted to obtain optimal HER2 protein expression thresholds predictive of HER2 status (by standard IHC or in situ hybridization [ISH]) and of survival benefit after anti‐HER2 therapy. Results: Absolute HER2 amol/μg levels were significantly correlated with both HER2 IHC and amplification status by ISH (p < 0.0001). A HER2 threshold of 740 amol/μg showed an agreement rate of 94% with IHC and ISH standard HER2 testing (p < 0.0001). Discordant cases (SRM‐MS‐negative/ISH‐positive) showed a characteristic amplification pattern known as double minutes. HER2 levels >2200 amol/μg were significantly associated with longer disease‐free survival (DFS) and overall survival (OS) in an adjuvant setting and with longer OS in a metastatic setting. Conclusion: Quantitative HER2 measurement by SRM‐MS is superior to IHC and ISH in predicting outcome after treatment with anti‐HER2 therapy. Highlights: We quantified by mass spectrometry the levels of HER2 in HER2‐positive breast tumors. The tumors with the highest HER2 levels benefitted most from HER2 inhibition. HER2 protein levels were better predicting markers than gene amplification. Double minute amplification pattern was associated with low HER2 levels.